Clinicopathological Profile of Dengue Infection in a Tertiary Care Centre in Nepal - Thapa, Bibechan; Pandey, Aakriti; Gautum, Santosh; KC, Sajana; Chhetri, Prabha Devi; Pokhrel , Estory; Poudel, Sangeeta; Shankar, P Ravi (Journal of Nepal Health Research Council, 2023)
Background:Dengue is a mosquito-borne viral disease with a wide spectrum of presentations ranging from subclinical disease to severe dengue. Dengue is endemic to the Terai of Nepal. Interestingly, an increasing incidence has been reported from hilly areas like Kathmandu valley. This study explored the clinicopathological profile of dengue infection. Methods:A total of 84 serologically confirmed dengue cases from September to November 2019 at KIST Medical College were recruited in a cross-sectional study after obtaining ethical approval. Dengue was categorized as dengue without warning signs, dengue with warning signs, and severe dengue. Clinicopathological information was recorded in the proforma by reviewing patients’ records. A descriptive statistical tool and chi-square test were carried out. Results: Out of 84 patients, 76% (64) were dengue without warning signs, 21.4% (18) were dengue with warning signs and 2.4% (2) were severe dengue. About 97.6% (82) presented with fever. During the course of illness, anemia was identified in 38.1% (32), thrombocytopenia in 65.5% (55), hemoconcentration in 6% (5), and leucopenia in 82.1% (69). Similarly, elevated aspartate transaminase and alanine transaminase (ALT) was observed in 67.7% (42) and 53.2% (33) respectively. The severity of dengue on presentation to hospital was significantly associated with thrombocytopenia, leucopenia, and elevated ALT. Similarly, the severity during course of illness in hospital was significantly associated with hemoconcentration, thrombocytopenia, leucopenia, and elevated ALT.Conclusions: Most common presentation of dengue infection was fever. The most common laboratory abnormalities were leucopenia, thrombocytopenia, hemoconcentration, anemia, and elevated liver enzymes. Awareness of these clinical and laboratory parameters is important for the prompt diagnosis, severity estimation, and overall management of dengue infection.Keywords: Biochemical; dengue; hematological; Nepal; serological